Associations of bisphenol A and polychlorinated biphenyls with spermatogenesis and steroidogenesis in two biological fluids from men attending an infertility clinic - Vítků, Jana; Heráček, Jiří; Kolátorová Sosvorová, Lucie; Hampl, Richard; Chlupáčová, Tereza; Hill, Martin; Sobotka, Vladimír; Bičíková, Marie; Stárka, Luboslav (Environment international, 2016)
BACKGROUND: In the testis, steroid hormones play an important role in spermatogenesis, the production of semen, and the maintenance of secondary sex characteristics and libido. They may also play a role as a target for substances called endocrine disruptors (EDs). As yet, however, no complex study has been conducted evaluating the relationships between EDs and the steroid spectrum in the plasma and seminal plasma. OBJECTIVES: To shed more light into mechanisms of EDs and the effects of bisphenol A (BPA) and polychlorinated biphenyls (PCBs) on human spermatogenesis and steroidogenesis. METHODS: We determined BPA and 11 steroids in the plasma and seminal plasma of 191 men with different degrees of fertility, using a newly developed liquid-chromatography mass spectrometry method. Concurrently, plasma levels of 6 congeners of PCBs, gonadotropins, selenium, zinc and homocysteine were measured. Partial correlations adjusted for age, BMI and abstinence time were performed to evaluate relationships between these analytes. RESULTS: Seminal BPA, but not plasma BPA, was negatively associated with sperm concentration (r=-0.198; p=0.009), sperm count (r=-0.178; p=0.018) and morphology (r=-0.160; p=0.044). Divergent and sometimes opposing associations of steroids and BPA were found in both body fluids. The sum of PCB congeners was negatively associated with testosterone, free testosterone, the free androgen index and dihydrotestosterone in plasma. CONCLUSION: BPA may negatively contribute to the final state of sperm quality. Moreover, our data indicate that BPA influences human gonadal and adrenal steroidogenesis at various steps. Environmental levels of PCBs negatively correlated with androgen levels, but surprisingly without negative effects on sperm quality.
Keywords: Endocrine Disruptors; dospělí; Gonadal Steroid Hormones; Polychlorinated Biphenyls; spermie; Adult; Semen; benzhydrylové sloučeniny; Spermatozoa; fenoly; testosteron; polychlorované bifenyly; Phenols; endokrinní disruptory; lidé; Chromatography, Liquid; sperma; Sperm Count; Humans; Infertility, Male; Benzhydryl Compounds; Male; pohlavní steroidní hormony; Testosterone; mužská infertilita; mužské pohlaví; počet spermií; chromatografie kapalinová; Spermatogenesis; spermatogeneze